CSIS: Cloud Service Identification System - Siddharth Arun; Aakash Chandrasekaran; Prakash P (International Journal of Electrical and Computer Engineering (IJECE), 2017)
To meet the need of the computational power, most of the users may go for a cloud based services for its scalability, flexibility and reliability. Cloud services have become an integral part of IT and analytical enterprises. Owing to increase in necessity of commercial cloud products being readily available, it has become extremely difficult for users to identify suitable cloud services. This paper proposes the recommender system precisely designed for the discovery of cloud services. Though there is an exponential increase in demand for cloud services, the amount of research done in this particular field is abysmal. Cloud Service Identification System (CSIS) crawls through Internet, identifies cloud services and stores them in a database. The user’s search query is processed and recommends cloud services accurately.